Pengembangan Aplikasi E-Smes Berbasis Android dengan Waterfall Method Sebagai Solusi Pemasaran dan Pengelolaan Usaha UMKM - Tri Kurniawati; Mentari Ritonga; Jean Elikal Marna; Yenni Artati; Wening Patmi Rahayu (Universitas Negeri Padang, 2021)
Cooperatives and MSMEs (Micro, Small, and Medium Enterprises) are some of the sectors that make a positive contribution to economic growth in Indonesia. The contribution obtained from the existence of MSMEs to GDP reaches 60% with the employment of 116.7 million people or 97.02% of the total workforce that is already working. Even though they have a big role, on the one hand, MSMEs have not been able to optimally manage their business, especially related to business management. The majority of MSME actors have not benefited from the use of digital technology because most MSME business actors have not fully understood the importance of using digital technology. The E-SMEs applications that will be developed for partners in this research are applications built using Java Enterprise Edition (JEE) technology. Java Enterprise Edition technology is a Java development for enterprise solutions, ranging from web-based applications using servlets and JSPs and android-based applications. The advantages of Java Enterprise Edition technology can create a reliable and portable application because Java can be implemented on various platforms and operating systems. In making this application using the Waterfall method which refers to the system development process model called the System Development Life Cycle (SDLC). This research method is a research and development method with the ADDIE approach. The developed e-SMEs application can later be used by Fiara Sulam to do online marketing and also digitally manage their finances.Keywords : E-SMEs MSMEs; Business Management